Mammals recorded during a one-day visit to Bako National Park, Sarawak, Borneo - Mohd Ridwan, Abd Rahman; Roberta Chaya, Tawie Tingga (Ecologyasia, 2017)
A total of four species of mammal comprising two primates, one rodent and one artiodactyl were recorded around Bako National Park headquarters (HQ). These mammals have previously been documented within the park as follows: Nasalis larvatus , Macaca fascicularis and Callosciurus sp. and Sus barbatus.